2004
DOI: 10.3349/ymj.2004.45.suppl.41
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic Differentiation of Mesenchymal Stem Cells and Its Clinical Applications

Abstract: Tissue engineering has the potential to provide cartilaginous constructs capable of restoring the normal function of native articular cartilage following joint injury or degradation. One approach to functional tissue engineering of cartilage involves the in vitro cultivation of tissue constructs by using: (i) chondrogenic cells that can be selected, expanded, and transfected to overexpress the genes of interest, (ii) scaffolds that provide a defined three-dimensional structure for tissue development and biodeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 0 publications
2
55
0
3
Order By: Relevance
“…Therefore, the induction of cell division in adult and OA cartilage remains an open subject. Recent studies point out the possibility of inducing chondrocyte proliferation by using novel techniques such as tissue engineering [37], mesenchymal stem cells [38], and dedifferentiated articular chondrocytes [39], in an attempt to restore the functional chondrocyte population in OA cartilage. These approaches shed more light on this subject.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the induction of cell division in adult and OA cartilage remains an open subject. Recent studies point out the possibility of inducing chondrocyte proliferation by using novel techniques such as tissue engineering [37], mesenchymal stem cells [38], and dedifferentiated articular chondrocytes [39], in an attempt to restore the functional chondrocyte population in OA cartilage. These approaches shed more light on this subject.…”
Section: Discussionmentioning
confidence: 99%
“…For chondrocytic differentiation in vitro of MSCs, it had been demonstrated that TGF-β was necessary for induction in vitro (Worster et al, 2001;Indrawattana et al, 2004;Lisignoli et al, 2005;Bai et al, 2004;Lee et al, 2004;Chen et al, 2003). In addition, other inducers were supplemented for chondrogenic induction, such as CDMP-1 (Bai et al, 2004), BMP (Indrawattana et al, 2004;Lee et al, 2004), GDF-5 (Lee et al, 2004), IGF-I (Worster et al, 2001;Zhang et al, 2004a;Indrawattana et al, 2004) or dexamethasone (Mackay et al, 1998). TGF-β induced-chondrogenesis was regulated through ERK1/2 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Viability of these cells was checked by trypan blue dye exclusion test. Cells in differentiation medium were also stained with oil Red O (for adipocytes), von Kossa (for osteocytes), and alcian blue 39 (for chondrocytes) on day 14.…”
Section: Perturbation Experiments To Assess Signaling Pathwaysmentioning
confidence: 99%